TEKNIK SINEMATOGRAFI PADA INSTAGRAM SEBAGAI STRATEGI KOMUNIKASI PEMASARAN (Studi Kasus Pada Cinematic Wedding di Instagram @panic.artwork): Studi Kasus Pada Cinematic Wedding di Instagram @panic.artwork - Septiawan, Naufal Rafiif; Suryo, Herning; Muadz, Muadz (Solidaritas, 2024)
This research discusses the role of Cinematography Techniques, a method that combines videoand text to produce professional visuals, especially in the context of Wedding Cinematography.One of the service providers that applies Cinematography Techniques is Panic ArtworkPhotography in Surakarta, founded by Rijal Nasyirul Haq in 2014. They use this technique asa marketing communication medium, creating high-quality cinematic weddings to attract theattention of prospective brides and grooms and increase the number of customers they have.Purpose The research is to describe the role of Cinematography Techniques on Instagram asa marketing communication strategy on the @panic.artwork account. Through qualitativeresearch with a case study approach, this research aims to understand how CinematographyTechniques function as marketing communications that attract consumer attention. By usingCinematography Theory and Marketing Mix, this research proves that CinematographyTechniques in cinematic wedding marketing are effective in attracting consumer interest viathe Instagram platform. The research results concluded that Cinematography Techniques onInstagram, especially by @panic.artwork, use angle shot, type shot, composition, continuityand cutting as the main keys to involving the bride and groom and strengthening marketingmessages. Panic Artwork intelligently utilizes Cinematography techniques as the main strategyin the "Promotion" element of the marketing mix, while other elements such as Product, Priceand Place are also well optimized. Innovations in Cinematography Techniques enable PanicArtwork to create stunning and meaningful visual content, increasing the appeal of each workpromoted.